POLICY IMPLEMENTATION ON TEACHER’S COMPETENCY IMPROVEMENT AT AR-RAUDLATUL HASANAH ISLAMIC BOARDING SCHOOL MEDAN - Rasyidin Rasyidin; Dja'far Siddiq (INTERNATIONAL JOURNAL ON LANGUAGE, RESEARCH AND EDUCATION STUDIES, 2018)
This study aims to describe the program of teacher competency improvement, efforts in improving teacher competence, financial policy in improving teacher competence, constraints faced in improving teacher competence, and efforts made in overcoming obstacles to improve teacher competence in Ar-Raudlatul Hasanah Islamic Boarding School Medan. Data collection techniques used were observation, interview, and documentation study. Data management consists of data reduction, data display / data presentation, data analysis, techniques to ensure the validity of research results. The results of the study revealed that the first program to increase the competence of teachers in Ar-Raudlatul Hasanah Islamic Boarding School Medan is the improvement of education qualification, equalization and certification, competency-based integrated training, education supervision, empowerment of Subject Teacher Consultant (MGMP), symposium, and other traditional training. The effort of developing the competence of teachers in Ar-Raudlatul Hasanah Islamic Boarding School Medan is by conducting education and training such as training, internship activities, school partnerships, tiered training and special training, short courses of LPTK or other educational institutions, internal coaching of schools and further education. Activities other than education and training are discussions, seminars, workshops. Obstacles in increasing the competence of teachers in Ar-Raudlatul Hasanah Islamic Boarding School Medan is influenced by factors such as structural factors, teacher personal factors, teacher economic factors, social factors, and cultural factors. Efforts to overcome the obstacles to increase the competence of teachers in Ar-Raudlatul Hasanah Islamic Boarding School Medan is always doing communication, monitoring and evaluation to ensure that the planned program can be implemented in accordance with the objectives, how far the achievement. Keywords:     Policy Implementation, Teacher’s Competence Improvement,                        Ar-Raudlatul Hasanah Islamic Boarding School